2017
DOI: 10.1177/0218492316688416
|View full text |Cite
|
Sign up to set email alerts
|

Topical and low-dose intravenous tranexamic acid in cyanotic cardiac surgery

Abstract: Background Coagulopathy is a major problem in surgery for cyanotic congenital heart disease. Tranexamic acid has been used both topically and systemically and plays a vital role in pediatric cardiac surgery by reducing blood loss and blood product requirement. We aimed to determine the anti-fibrinolytic effectiveness of low-dose systemic or topical tranexamic acid or a combination of both. Methods Seventy-five patients were divided in 3 groups of 25. Group A patients were given tranexamic acid 20 mg kg intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Between 2000 to 2016, seven small RCTs comparing the IP application of TxA vs placebo were reported in cardiac surgery . In all these trials, except one using a small dose, topical application of TxA significantly reduced the 24‐hour postoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Between 2000 to 2016, seven small RCTs comparing the IP application of TxA vs placebo were reported in cardiac surgery . In all these trials, except one using a small dose, topical application of TxA significantly reduced the 24‐hour postoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2000 to 2016, seven small RCTs comparing the IP application of TxA vs placebo were reported in cardiac surgery. [16][17][18][19][20][21][22][23][24][25] In all these trials, except one using a small dose, topical application of TxA significantly reduced the 24-hour postoperative blood loss. We performed a meta-analysis of these trials and confirmed the substantial reduction in 24-hour blood loss with topical application of TxA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the combination of low dose systemic TXA and topical TXA intrapericadially before chest closure was the best. 22 In a clinical review, William and colleagues observed that practice of TXA as antifibrinolytic in intra-op and peri-op settings has strong pharmacological and clinical grounds. They found that TXA can be used effectively in adult cardiac surgery, paediatric cardiac and non-cardiac surgery, orthopaedic surgery, neurosurgery, hepatic surgery, and gynaecology and obstetrics surgeries.…”
Section: Discussionmentioning
confidence: 99%